An Overview of Culinary and Medicinal Mushrooms in Neurodegeneration and Neurotrauma Research - Wong, Kah Hui; Ng, Chai Chee; Kanagasabapathy, Gowri; Yow, Yoon Yen; Sabaratnam, Vikineswary (Begell House, 2017)
Culinary and medicinal mushrooms have been appreciated since prehistoric times as valuable resources for food and medicine. Edible mushrooms represent an untapped source of nutraceuticals and valuable palatable food. Long considered tonics, they are now treasured as functional foods that can improve human health and quality of life. Numerous studies have provided insights into the neuroprotective effects of edible mushrooms, which are attributed to their antioxidant, antineuroinflammatory, and cholinesterase inhibitory properties, and their ability to prevent neuronal death. Here we review the recent literature on the role of culinary and medicinal mushrooms in the management of neurodegenerative diseases and neurotrauma. We highlight some of the molecular mechanisms for how these alternative medicines provide health benefits that could help us to harness their neuroprotective effects.